Adults with type 1 diabetes: Partner relationships and outcomes. (March 2017) - Trief, Paula M; Jiang, Yawen; Beck, Roy; Huckfeldt, Peter J; Knight, Tara; Miller, Kellee M; Weinstock, Ruth S
Health outcomes of adults with type 1 diabetes may be affected by relationship status and quality. Our objective was to examine associations between relationship status, relationship factors, and outcomes in adults with type 1 diabetes. N  = 1660 participants completed surveys measuring relationship satisfaction and perceived partner support style (active engagement, protective buffering, over-protection). Differences in glycemic control and adherence for those married/partnered versus not were insignificant. Higher relationship satisfaction, and having an engaged, not over-protective, partner was associated with better glycemic control and self-care. Helping partners support patients, avoiding over-protection, may enhance relationship and diabetes-related patient outcomes for adults with type 1 diabetes.